EVALUATING THE MANAGEMENT AND MAINTENANCE PRACTICES OF LINEAR ACCELERATOR AND COBALT-60 CANCER TREATMENT MACHINES IN NIGERIA: A COMPREHENSIVE ASSESSMENT (Jurnal Mekanikal, 2023)
This research paper investigated the state of radiotherapy machines and their management in cancer treatment centers in Nigeria. The study aimed to identify the challenges faced by these centers and propose strategies for improvement. Through a comprehensive analysis of data collected from surveys and questionnaires, critical issues impacting the availability, reliability, and effectiveness of radiotherapy machines were highlighted. The findings revealed a significant shortage of radiotherapy machines across the nation, with Nigeria having less than 6% of the required number of linacs. This scarcity led to a high workload on the existing machines, resulting in long waiting lists and compromised treatment outcomes. Management challenges, such as the absence of preventive maintenance policies, inadequate personnel training, delayed spare parts delivery, and limited engagement of maintenance contractors, were identified. The research emphasized the need for supportive cancer treatment machines, including orthovoltage and superficial machines, to alleviate the burden on existing radiotherapy machines. However, most centers lacked these supportive machines, limiting their ability to provide comprehensive care to patients. Financial sustainability also emerged as a significant concern, as internal funds proved insufficient for maintenance and operations. The involvement of the government and the establishment of independent regulatory bodies were proposed to address these challenges. In conclusion, this study called for urgent action to address the gaps and challenges in radiotherapy machine management in Nigeria. It highlighted the importance of increasing the number of machines, implementing preventive maintenance policies, enhancing staff training, and securing adequate funding. By doing so, the quality of cancer care could be significantly improved, leading to better patient outcomes and a more robust healthcare system in Nigeria.
Keywords: Cancer; Linear Accelerator; Cobalt-60 Machines; Maintenance